Draft Annual Plan 2000-2001 Special Component Plan - Planning Commission (Planning Commission, 2000)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast, about 162 kms. south of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of Villupuram district and Cuddalore District of Tamilnadu. Karaikal region is about 150 Kms. south of Pondicherry and it is surrounded by Nagapattinam District of Tamilnadu. Yanam region is located about 8^-0 kms. north east of Pondicherry near Kakinada in Andhra Pradesh.
Government of Pondicherry Planning and Research Department